Broken three times: a story of child abuse in America - Kaufman, Joan (Oxford University Press, 2016)
"Broken Three Times is a narrative nonfiction book that chronicles one family's travails through the child welfare system. While this is the story of one family, it typifies countless others who get lost in the system. Each chapter of the family's story provides a launching point for discussing contemporary policy and practice, while it presents scientific updates relevant for understanding risk and promoting resilience in maltreated children, and improving the child welfare system. Emerging insights from genetics and neuroscience research are also reviewed. The book begins with snapshots from the mother's abusive childhood, which sets the stage for discussing trauma-informed systems of care initiatives. These programs include efforts to train professionals on the effects of trauma, implement universal screening of trauma experiences, and disseminate evidence-based treatments to address trauma-related psychiatric problems. The book then fast-forwards to the family's first involvement with Connecticut protective services when the children are eleven and ten. After a brief investigation, the family's case is closed, and despite their many needs, the family is not provided links to any ongoing supportive services. This chapter is then followed by a brief discussion of differential response programs. Like many unconfirmed cases, the family is re-referred to protective services within months of the initial case closing, and after a lengthy second investigation, the children are removed from their mother's care. Over the next five years we see the children pass through nearly twenty placements, while their mother continually relapses on crack and moves from one violent relationship to the next. The prevalence of substance abuse and domestic violence problems in families referred to protective services are also reviewed, together with a range of other issues relevant to improving the child welfare system and the outcomes of the children it serves. Over the course of the decade that is covered in the book's primary narrative, the child welfare system has started a process of significant reform. Trauma-informed systems of care, differential response teams, and strengthening of community-based mental health and addiction services are just a few trends that have begun to transform the system and improve the trajectory of children entering care in many jurisdictions. Judgment is still out on whether these changes will last and will prove effective, but stories li ...